Production Process Optimisation: Implementation of Modern Ecoheat Technology Innovation to Improve Efficiency and Quality of Exported Sea Cucumber Products at Ukm Mitra Bintang Laut in Palu City - Maruka, Safriyanto S; Novitasari, Maya; Salam, Miming Berlian Hi. B.; Wirdha, Wirdha; Fitramadan, Lis; Syaifuddin, Syaifuddin; Nurfadilah, Nurfadilah (Unram Journal of Community Service, 2024)
The implementation of Modern EcoHeat Technology Innovation is designed to overcome the challenges of the non-standardised sea cucumber drying process. This programme is conducted in several stages, namely: Installation of EcoHeat drying technology in the production facilities of partner SMEs, training on the use of technology for employees and students, development of quality SOPs, and improvement of logistics management for more efficient distribution. This activity also includes regular evaluation of production processes and results to ensure improved product quality according to international standards. In addition, a social media campaign was implemented to support product marketing and increase consumer awareness about the benefits and quality of dried sea cucumbers from Bintang Laut SMEs. The results of the programme showed significant improvements in the efficiency of the production process, which enabled Bintang Laut SME Partners to increase production capacity and reduce operational costs. Improved product quality of dried sea cucumbers with more consistency and longer shelf life was also achieved, resulting in a positive response from the market. The programme also successfully enhanced employee skills through technology training and quality SOPs. The programme successfully optimised the production process with the support of modern technology and better implementation of quality SOPs. The programme was able to improve the competitiveness of dried sea cucumber products in the export market and provide opportunities for SMEs to maintain quality and expand markets